Proposta de redução no consumo energético e estudo de geração fotovoltaica na sede Ecoville da UTFPR - Krasnhak, Larissa Barbosa (2019)
Civil construction is the sector that most contributes to the generation of solid, liquid and gaseous wastes and is also the one that consumes the most natural resources. In fact, the sector presents great potential for environmental recovering, besides to promoting sustainable development. This paper presents a proposal to reduce electric energy consumption in the lighting and air conditioning system in buildings of the Curitiba campus of the Federal Technological University of Paraná – Ecoville. The need to replace some equipment arises through the existence of more efficient ones, which provide the same work, but with reduced energy expenditure. The work also presents a study for the installation of an on grid at the University campus, allowing the generation of electric energy at the point of consumption. Since photovoltaic solar energy is considered inexhaustible and clean, it is an alternative for the diversification of the country’s electrical matrix, which is currently predominantly hydraulic. The study’s literature is based on the importance of sustainable buildings, presents a review on lighting and air conditioning systems, principles of photovoltaic solar energy and the panorama of the application of this technology in Brazil and in the world. Once the study sites were determined, A, B, C, EF and IJ buildings, the case study method was applied to the lighting system, the air conditioning system and the solar photovoltaic system. A consumption scenario was created to estimate system expenditures based on the energy bills of the consumer unit. The proposed replacement of lighting equipment currently used by LED technology has resulted in a 47% reduction in energy consumption and the replacement of air conditioning equipment with more efficient models provides a 9% reduction in energy expenditure. The photovoltaic systems were dimensioned in the coverage of each block and in the whole they have nominal power of 129.57 kW and the generation expectation is on average 12,797 kWh/month, this value represents 19% of the Ecoville buildings current consumption and 29% of consumption considering the replacement of the equipment proposed in the study.